Immediately loaded fixed full-arch implant-retained prosthesis: a solution to the extreme defect in zone 2—a case report - Lu, Xiaoya (2023)
Implants immediately loaded full-arch prosthesis in maxilla is always a challenge, especially when the zone 2 is extremely defected. To achieve a satisfying result, different therapeutic alternatives have been proposed, such as zygomatic implant, pterygoid implant; however, precise surgical skills limited its application.